Maharishi Vedic University in Cambodia: A Study of Three Mature-Age Graduates - Fergusson1, Lee; Bonshek, Anna; Pau, Maria (ASEAN Journal of Education, 2019)
This study forms part of a 25-year research program begun by these authors in 1993 at Maharishi Vedic University (MVU) in Cambodia. Prior research includes eight published studies and two monographs on: the history of higher education and teacher education in Cambodia documenting areas such as curricula, enrolments, government expenditures, social and cultural contexts, and educational futures; learning and student attitudes; impacts of Vedic Science-based education on non- verbal intelligence and personality, including depression and anxiety; an assessment of the social and economic contributions of MVU compared to baseline national and regional data from Thailand, Vietnam and Lao PDR; and the reduction of socio-political violence and increased social coherence in Cambodia between 1990 and 2008. The present study, using standard case study techniques, investigates the lives of three former undergraduate management students of MVU and provides qualitative evidence of personal and professional experiences before, during and after studying at the university to test the proposition that participation in a curriculum of Vedic Science-based education in Cambodia is associated with long-term salutary benefit in the lives of students. Results indicate that as a result of studying at MVU, all three graduates, despite harsh and difficult upbringings in rural Cambodia, significantly increased their self-sufficiency, confidence, and health and healthy lifestyles, reduced stress, and enhanced their creativity, moral reasoning, and intelligence. This study contributes to an understanding of the general reconstruction of higher education in Cambodia since the early 1990s.